2018
DOI: 10.1111/iej.13027
|View full text |Cite
|
Sign up to set email alerts
|

Chemical biofilm removal capacity of endodontic irrigants as a function of biofilm structure: optical coherence tomography, confocal microscopy and viscoelasticity determination as integrated assessment tools

Abstract: Aim To investigate the influence of biofilm structure on the biofilm removal capacity of endodontic irrigants and to study changes in the architecture of the remaining biofilms. Methodology Streptococcus oralis J22 and Actinomyces naeslundii T14V‐J1 were cocultured under different growth conditions on saliva‐coated hydroxyapatite discs. A constant depth film fermenter (CDFF) was used to grow steady‐state 4‐day biofilms. Biofilms were grown under static conditions for 4 and 10 days within a confined space. Twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
135
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(138 citation statements)
references
References 46 publications
1
135
1
1
Order By: Relevance
“…, Busanello et al . ). Finally, the importance of saliva conditioning in the co‐adhesion of the particular bacterial species used in this study has been already demonstrated (Bos et al .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…, Busanello et al . ). Finally, the importance of saliva conditioning in the co‐adhesion of the particular bacterial species used in this study has been already demonstrated (Bos et al .…”
Section: Discussionmentioning
confidence: 97%
“…) and biofilm structure (Busanello et al . ) are all factors that influence the response of biofilms to the applied biocides. In particular, a recent study has demonstrated that steady‐state, dual‐species, gram‐positive biofilms, grown on saliva‐coated hydroxyapatite discs, showed dense bacterial presence and low content in extracellular polymeric substances (EPS) and were less prone in 2% NaOCl‐mediated dissolution (Busanello et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations